Investigation of Thermal, Mechanical, and EMI Shielding Response of PEI/PET Polymer Blends - Kaftelen-Odabasi, Hulya; Olmosovich, Elshod Khakberdiev; Berdinazarov, Qodirbek Nuridin Ugli; Dusiyorov, Nizomiddin Zokir Ugli; Ashurov, Nigmat Rustamovich; Odabasi, Akin; Helhel, Selcuk (Institute of Electrical and Electronics Engineers Inc., 2025)
Effects of electromagnetic waves; in electrical-electronic devices, it is seen in the form of corrupt signals, sudden power cuts, power fluctuations, damage or unusable electronic devices, and a decrease in life and performance in the electronic system. Therefore, electromagnetic interference (EMI) shielding continues to attract interest in areas ranging from commercial and scientific electronic instruments used in our everyday life to aerospace systems and military electronic products. Due to their low cost, lightness, high corrosion resistance, flexibility in design, good processability, and high specific EMI shielding effectiveness, polymer composite materials are becoming an interesting alternative for shielding applications, overcoming the limitations of metal shielding. Polymer blends are considered to be important matrix materials for polymer composites containing conductive and magnetic fillers for electromagnetic interference (EMI) protection. This study involved preparing different ratios of Polyetherimide/Polyethylene terephthalate (PEI/PET) polymer blends (90/10, 70/30, and 50/50 by weight) using a twin-screw extruder and hot pressing. The thermal, mechanical properties, and EMI performances of the polymer blends were investigated as matrix materials for polymer composites used in electromagnetic interference shielding. According to the results of the thermal analysis, a difference of approximately 10°C in the glass transition temperature is observed as the percentage of PET in the PEI/PET blend decreases, indicating that PET and PEI are relatively miscible with each other. The mechanical properties of the blends showed that as the amount of PET increased, the modulus of elasticity decreased from 1158N/m2 for pure PET to 1120N/m2 for PEI/PET 50/50 composition. The maximum shielding efficiency was found to be 2.54 dB in PEI/PET polymer blends at a ratio of 70/30. © 2025 IEEE.
8th International Electromagnetic Compatibility Conference, EMC Turkiye 2025 -- 14 September 2025 through 7 September 2025 -- Antalya -- 214230
Keywords: elastic modulus; EMI shielding; polymer blending; thermal properties